ANALISIS ERGONOMI TERHADAP MEJA SERBAGUNA MINIMALIS - Muhamad Zainudin; Gilang Rusadi Ahmad; Faisal Amin (Universitas Mercu Buana, 2021)
At this time there are many creative industries that make products to make it easier for consumers. We need a product that has a versatile function, is minimalistic, and doesn't take up much space or it can also be called a product that must have its own ergonomic function. Ergonomics analysis on the design of a minimalist multipurpose table frame aims to analyze the ergonomics of a minimalist multipurpose table in terms of the user's comfort level and suitability with the user's body posture and determine the cost per unit of the product of the minimalist multipurpose table design.In this study using a quantitative approach method. This method is used to examine certain populations or samples, data collection using research instruments, data analysis is quantitative/statistical, with the aim of testing predetermined hypotheses. The design process is carried out through several stages including field observations, literature studies, and questionnaires as well as interviews with resource persons.A minimalist multipurpose table frame made of iron and wood with a shelf height of 115 cm, a table height of 75 cm, a distance between the two table legs of 120 cm, and a table leg width of 50 cm. The results obtained from this study are above 85% or which can be categorized as very good. That way, it can be said that this minimalist multipurpose table provides an ergonomic impact for consumers or respondents.